(untitled) (THE ACADEMIA, 2026)
This paper analyses the BRI deal from Nepal’s foreign policy perspective. Nepal, a Himalayan nation, is wedged between Asia’s two mega-nations, India and China, with Bangladesh at its bosom. Introduced in 2013 by President Xi Jinping, the Belt and Road Initiative, or BRI, is an ambitious effort to fund new infrastructure across the globe to promote enhanced connectivity between regions and greater trade between countries. Foremost among these is the BRI, which has had a significant impact on Nepal’s foreign policy after it signed a framework agreement to join the BRI. This paper examines how the BRI is relevant to both Nepal and China, starting with Nepal’s external relations and the requirements of economic and infrastructure development. This paper is a qualitative exploration using analytical and historical approaches. It provides a qualitative content analysis of texts related to Nepal’s BRI framework agreement and examines their possible implications for Nepal’s foreign relations. The paper argues that regardless of whether the BRI actually brings direct gains in future, it will definitely have a significant impact on Nepali foreign policy and socio-economic vicissitudes. It will help stabilise Nepal’s economy and enhance regional connectivity. However, it also exposes the stigma of debt traps and layers in fraught geopolitical dynamics. Nepal, furthermore, walks on eggshells as a neighbour of China and India.